Prime time for the sweet spot in timing of coronary invasive approach in patients with non-ST elevation myocardial infarction - Navarese, Eliano P.; Wernly, Bernhard; Lichtenauer, Michael; Pepe, Martino; Wanha, Wojciech; Ferrante, Giuseppe; Frediani, Lara; Veulemans, Verena; Zeus, Tobias; Westenfeld, Ralf; Jung, Christian; Gurbel, Paul A. (Journal of Thoracic Disease, 2017)
Acute coronary syndromes (ACS) continue to represent a major cause of morbidity and mortality worldwide. In the past decade data from the United States and Europe reported decreased incidence of ST-elevation myocardial infarction (STE-ACS) with an increase in non-ST-elevation myocardial infarction (NSTE-ACS) (1-3). As compared to STE-ACS patients, during initial admission, NSTE-ACS patients are at lower risk for death, but over time death rates become comparable with a trend towards increased mortality in the latter group (4). NSTE-ACS therefore constitutes a challenge in cardiology.